An analysis of figurative language in Michael Jackson’s songs album history: Past, Present and Future, Book I - William Haudinata Prakasa; Bramantya Pradipta (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2023)
This research seeks to identify Michael Jackson song lyrics include figurative language. As a result, the researcher came up with a question to represent the issue. What forms of figurative language does Michael Jackson utilize in his songs Album History: Past, Present and Future, Book I? According to this study, Figurative language comes in 12 different types such as Simile, Metaphor, Personification, Allusion, Anaphora, Idiom, Onomatopoeia, Metonymy, Synecdoche, Hyperbole, Syntax, Repetition, and Imagery are some of its forms. This research is made by William Haudinata Prakasa from Universitas 17 Agustus 1945 Surabaya. The researcher employed a qualitative approach since the data were gathered utilizing word documents and a method of systematic context text analysis (words, phrases, lines, and sentences). By categorizing words with similar meanings, qualitative analysis enables researchers to comprehend the text. The researcher used 20 songs from Michael Jackson Songs Album History: Past, Present and Future, Book I as a tool to identify the data that will be studied based on this research. According to the research, there are 86 datas from each Michael Jackson's songs, including 21 personifications, 23 metaphors, 20 hyperboles, 5 repetitions, 5 similes, 2 idioms, 1 imagery, 2 allusions, 2 anaphoras, 1 onomatopoeia, 1 metonymy, and 3 synecdoches.